Risk factors for prolonged hospital stay after isolated coronary artery bypass grafting - Oliveira,Elayne Kelen de (2013)
INTRODUCTION: Characteristics of the patient and the coronary artery bypass grafting may predispose individuals to prolonged hospitalization, increasing costs and morbidity and mortality. OBJECTIVE: The objective of this study was to evaluate individual and perioperative risk factors of prolonged hospitalization in intensive care units and wards. METHODS: We conducted a case-control study of 104 patients undergoing isolated coronary artery bypass grafting with cardiopulmonary bypass. Patients hospitalized >3 days in the intensive care unit or >7 days in the ward were considered for the study. The association between variables was estimated by the chi-square test, odds ratio and logistic regression; P <0.05 was considered statistically significant. RESULTS: Hospital stay >3 days in the intensive care unit occurred for 22.1% of patients and >7 days in the ward for 27.9%. Among preoperative factors, diabetes (OR=3.17) and smoking (OR=4.07) were predictors of prolonged intensive care unit stay. Combining the pre-, intra-and postoperative variables, only mechanical ventilation for more than 24 hours (OR=6.10) was predictive of intensive care unit outcome. For the ward outcome, the preoperative predictor was left ventricular ejection fraction <50% (OR=3.04). Combining pre- and intraoperative factors, diabetes (OR=2.81), and including postoperative factors, presence of infection (OR=4.54) were predictors of prolonged hospitalization in the ward. CONCLUSION: Diabetes and smoking were predictors of intensive care unit outcome, and ejection fraction <50% of ward outcome. For the set of perioperative factors, prolonged hospitalization after isolated coronary artery bypass grafting was associated with mechanical ventilation >24 hours for the intensive care unit and presence of infection for the ward.